1972
DOI: 10.1037/h0032859
|View full text |Cite
|
Sign up to set email alerts
|

Precocious thoughts on number: The long and the short of it.

Abstract: One hundred and sixty-three 3-, 4-, 5-, and 6-year-old children were tested on seven conservationlike number problems. Five were problems of inequivalence and two were problems of equivalance. All problems were presented in a static form so that the children did not see a transformation away from one-to-one correspondence. Few children made the correct numeric judgments on all problems. The youngest performed as well as the oldest on specific problems of inequivalence similar to one used by Mehler and Bever, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
3

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 9 publications
3
27
3
Order By: Relevance
“…These results support the analyses of Gelman (1972) and Pufall and Shaw (1972) of the development of number concepts in young children in which the child is assumed to gradually learn how to discriminate various dimensions (such as length and density) as irrelevant to number. The characteristics of the constituent members of the set, as opposed to their spatial relationships to each other, interfered with judgments of numerosity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results support the analyses of Gelman (1972) and Pufall and Shaw (1972) of the development of number concepts in young children in which the child is assumed to gradually learn how to discriminate various dimensions (such as length and density) as irrelevant to number. The characteristics of the constituent members of the set, as opposed to their spatial relationships to each other, interfered with judgments of numerosity.…”
Section: Discussionsupporting
confidence: 83%
“…Previous research concerning the development of number concepts in young children (e.g., Gelman 1972;Pufall & Shaw 1972;Siegel 1972Siegel , 1973Wohlwill 1960;Zimiles 1966) has indicated that certain perceptual factors other than numerical size influence a child's perception of numerosity. Both heterogeneity of the constituents of a set and variations in the spatial arrangement of the set have been found to influence a child's perception of numerosity.…”
Section: Heterogeneity and Spatial Factors As Determinants Of Numeratmentioning
confidence: 99%
“…Qualitatively similar results have been obtained with children (Pufall & Shaw, 1972); performance is more accurate with congruent stimulus pairs than with incongruent stimulus pairs. Pufall and Shaw (1972) suggest that children often use length cues to make their numerical judgments. Thus, they will tend to make more errors when the numerically larger row is shorter.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, young children make more errors with incongruent stimuli (in which the numerically larger row is shorter) than with congruent stimuli (Pufall & Shaw, 1972). Presumably, this effect occurs because length cues tend to be used to make the numerical comparison.…”
mentioning
confidence: 99%
“…Similar quantitative analyses have already proven themselves to be of value in other cognitive areas (Bausano & Jeffrey 1975;Pufall & Shaw 1972). An analysis of the quantitative values of relevant and irrelevant cues (e.g., comparing problem difficulties of two pairs of cars whose speeds differ by 50% with pairs whose speeds differ by 100%) could cast light on the information processing involved in solving problems related to time concepts.…”
Section: Iris Levin 443mentioning
confidence: 73%